Seroprevalence of Hepatitis B and C in Healthy Malaysian Adults: A Preliminary Report - Hui-min Neoh; Saberi bin Saimun; Rahman Jamal (Journal of Biomedicine and Translational Research, 2019)
none (letter to to editor format)